Pengaruh Penambahan Mfi Ionizer Terhadap Konsumsi Bahan Bakar dan Daya Motor Pada Mesin Diesel 4 Silinder - Idham Agung W.; I Made Muliatna (Otopro, 2006)
This research is conducted to exime fuel system in four cylinder diesel engine by comparing betwen standard fuel system consumption (without MR Ionizer) and fuel system consumption with MR Ionizer. The purpose of this research is to find out data about spesific fuel consumption (Sfc) and effective horse power (Ne/BHP) This experimental siudy is done by installing MFI Ionizer device on fuel system of Isuzu Panther 2000 four cylinder diesel engine. Then data obtained is analyzed by descriptif method. The results indicated that effective has improved until 1,67 %, comparing with standard, while sped c fuel consumption (Sfc) reised until 10,74 % (consumpt more fuel) than standard.